Cover Feature: NaBH4 Surface Modification on CeO2 Nanorods Supported Transition‐Metal Catalysts for Low Temperature CO Oxidation (ChemCatChem 17/2020). Issue 17 (4th September 2020) - Wang, Yifan; Liu, Zhongqi; Wang, Ruigang
Abstract : The Cover Feature shows a surface etching (doping and roughness) effect of CeO2 support on the CO oxidation activity of transition metal oxide catalysts. In their Full Paper, Y. Wang et al. explain that CeO2 nanorods support with a chemically etched rough surface readily releases lattice oxygen and promotes strong catalyst‐support interaction for better low temperature CO oxidation. The results show that the enhanced CO oxidation performance is mainly attributed to the surface defects (oxygen vacancies, Ce 3+ sites, and structural disorders) created by the boron‐doped CeO2 surface during NaBH4 chemical etching and to the strong metal‐support interaction. More information can be found in the Full Paper by Y. Wang et al.